1528Prospective Vs Retrospective Cohort Studies: Is a Consensus Needed?. (2nd September 2021) - Bashir, Maryam Mohammed; Maskari, Fatma Al; Ahmed, Luai; Al-Rifai, Rami H.
Abstract: Focus of Presentation: There is a confusion among epidemiologists, especially early-career epidemiologists, on the different definitions and use of prospective and retrospective cohort studies. There is a need for consensus by the expert community on this methodological dilemma. Findings: Different Epidemiology experts define prospective and retrospective cohort studies differently. Most textbooks define prospective cohort study as one conducted when all the subjects are outcome-free while in retrospective cohort study, at least some of them have developed the outcomes, then researchers go back in time to study exposures. However, some experts define both study types based on the time of development of the research hypothesis or question in relation to data collection. Some experts consider retrospective studies to be only from records. Meanwhile, some consider any follow up study to be prospective even if historical data is used. These disparities in definitions lead to confusion among young epidemiologists. Some experts state that there is no need to differentiate between the two studies, however, we are aware of the possible bias and confounding that could occur from retrospective studies. Conclusions/Implications: It has become essential for the expert community to address this methodological dilemma and to reach consensus on it. This could serve as a guide for young epidemiologists and ensure the uniformity of research worldwide. Key messages: There are disparities in definitions and use of prospective and retrospective cohort studies. Hence, the expert community, especially the International Association of Epidemiology, should address this dilemma and reach a consensus to form standard guidelines.